On a Conjecture about the Saturation Number of Corona Product of Graphs. (28th September 2022) - Tavakoli, Mostafa
Abstract : Let G = V G, E G be a simple and connected graph. A set M ⊆ E G is called a matching if no two edges of M have a common endpoint. A matching M is maximal if it cannot be extended to a larger matching in G . The smallest size of a maximal matching is called the saturation number of G . In this paper, we confirm a conjecture of Alikhani and Soltani about the saturation number of corona product of graphs. We also present the exact value of s G ∘ H where H is a randomly matchable graph.